Program TUMBUH JOSS: Pendekatan Door-to-Door untuk Identifikasi Faktor Risiko dan Peningkatan Pengetahuan Keluarga Anak Stunting di Wilayah Kerja Puskesmas Jetis Kabupaten Mojokerto - James Hadiputra Sunarpo; Ni Putu Alya Magfira C. P; Aidah Afkarina; I Made Kusuma Nurjaya; Katrina Fadilah Aisyah; Abdulloh; Syahrefi Alifio Kadir Talib; Suryani Pramita Sari; Atik Sri Wulandari; Wike Herawaty; Ayu Cahyani Noviana (Jurnal Riset Multidisiplin Edukasi, 2025)
Stunting is a major public health issue with long-term consequences for physical growth, cognitive development, and future productivity. The “TUMBUH JOSS” door to door program was conducted in the Jetis Public Health Center area on November 14, 2025, to improve family knowledge and nutritional practices among 17 stunted children. The activity began with team coordination, preparation of anthropometric tools, and collection of baseline data. Interventions included structured interviews, anthropometric measurements, home environment assessments, and personalized education on nutrition and infection prevention. Follow-up monitoring was carried out through the local health post. The program demonstrated increased parental understanding of feeding practices, household hygiene, selection of protein-rich foods, and stimulation for child development. The intervention successfully enhanced family engagement and supported behavioral changes toward healthier practices. This personalized home-visit approach proved effective in supporting stunting prevention and management at the household level.